A positive electric retention filtration accumulation solidification plugging method

By injecting a positively charged cured bridge leakage plugging slurry into the complex formation, a high-strength sealing layer is formed by injecting a positively charged cured bridge leakage plugging slurry into the complex formation, and an efficient and safe leakage plugging effect is achieved.

CN119752428APending Publication Date: 2025-04-04XINJIANG GRAND OILFIELD TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411891361.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing leak plugging technology has poor sealing effect in complex strata such as slotted strata, low pressure layer, crushed strata, etc., and commonly used polymer gels and cured leak plugging materials have problems such as low pressure bearing capacity and poor anti-drilling fluid pollution.

Method used

The positive electric retention filter loss accumulation and curing leakage plugging method is adopted to inject a positively charged cured bridge leakage plugging slurry into the formation, and the cured material in the leakage plugging slurry is retained on the surface of the leakage layer by using the charge, and a high-strength sealing layer is formed by bridge and filling of the bridge material.

Benefits of technology

The retention capacity of leak plugging slurry in the leak layer is improved, the sealing effect is ensured, it is suitable for different types of complex formations, and the construction process is safe and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200739990000061
    Figure BDA0005200739990000061
Patent Text Reader

Abstract

The present invention discloses a positively charged retention, filtration loss, accumulation, solidification and plugging method, which adopts a positively charged solidified bridging plugging slurry. Through charge attraction, the positively charged solidified material gradually stays on the surface of the leaking layer. Due to the friction effect, the migration speed of large particles in the leaking layer is slowed down, and gradually accumulates in the leaking layer to form a barrier. Under the action of the formation pressure difference, the solidified plugging slurry will gradually lose water, and the plugging section will gradually be compacted, thereby forming a high-strength segment plug to plug the leaking channel. The solidified bridging plugging slurry is composed of water, solidified material and bridging material. The present invention introduces a positively charged solidified material, which generates a potential change with the surface of the leaking layer through the action of the charge to make it retained and accumulated, and is combined with the bridging plugging material to form a plugging layer. Since the plugging slurry contains a solidified material, it can be solidified after losing water and has a high solidification strength, thereby ensuring the plugging effect of the leaking layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil and gas well plugging, in particular to a positive electric retention filtration loss accumulation solidification plugging method. Background Art

[0002] With the advancement of drilling technology and the innovation of equipment, the drilling depth continues to extend, and the probability of encountering complex formations such as fracture and hole leakage increases. The leakage problem is becoming more and more serious. The occurrence of well leakage increases the drilling cost, prolongs the drilling cycle, and even leads to the scrapping of the wellbore. At present, the commonly used plugging materials for drilling leakage include bridging plugging materials, high water loss plugging materials, shielding temporary plugging materials, polymer gel plugging materials and solidification plugging materials, among which bridging plugging materials and high water loss plugging materials mainly plug conventional leakage layers, but the plugging effect for complex leakage formations is not obvious; polymer gel and solidification plugging materials are often used to plug complex leakage formations, but there are shortcomings in actual applications, such as low pressure bearing capacity of polymer gel, complex on-site preparation, poor resistance to drilling fluid pollution, etc., and solidification plugging materials have poor retention effect, insufficient water invasion resistance, complex construction process, and poor resistance to drilling fluid pollution.

[0003] For example, patent CN114621740B provides a high-loss consolidation plugging agent, plugging slurry and its preparation method, which are used to solve the problem of crack and hole leakage. The high-loss consolidation plugging agent is composed of a toughening agent, a hardener, a filter aid, and a slag material. The plugging agent is prepared into a plugging slurry with a proportion of bentonite-based slurry, and is pumped into the well through a drilling tool. Under the pressure difference between the wellbore and the leaking layer, the filter aid diatomaceous earth or gypsum causes the plugging slurry to lose quickly; the hardener provides good reaction conditions for the solidification of the plugging slurry, so that it forms a tough filter cake in the leaking channel. The retention effect of the plugging slurry mainly depends on the pressure difference between the wellbore and the formation to cause it to lose water rapidly and form a mud cake to stay. It has high requirements for the leaking layer. If a large leaking channel is encountered, it is easy to flow to the deep formation under the pressure difference of the formation, and the plugging effect cannot be guaranteed. Summary of the invention

[0004] Aiming at the problem that the existing plugging technology has poor plugging effect on complex formations such as fractured formations, low-pressure formations, and broken formations, the present invention provides a positive electric retention filtration accumulation solidification plugging method.

[0005] The positively charged retention filtration accumulation solidification plugging method provided by the invention plugs leaks by injecting a positively charged solidified bridging plugging slurry into the formation.

[0006] The solidified bridging plugging slurry is composed of water, calcium bentonite, solidifying material and bridging material. Based on the weight of water, the weight of calcium bentonite accounts for 1-3% of the weight of water, the weight of solidifying material accounts for 15-30% of the weight of water, and the weight of bridging material accounts for 10-30% of the weight of water.

[0007] The curing material is any one of a cement curing system, a slag curing system and an epoxy resin curing system.

[0008] The cement curing system contains nano aluminum silicate, nano silicon dioxide and calcium oxide. Further preferably, the cement curing system includes the following components in parts by weight: 60-80 parts of oil well G grade cement, 0.5-1.5 parts of nano aluminum silicate, 1-3 parts of nano silicon dioxide, 0.5-1 parts of xanthan gum, 3-5 parts of calcium oxide, 5-15 parts of micro silicon, and 0-5 parts of floating beads.

[0009] The slag-based solidification system contains magnesium oxide, aluminum oxide, calcium oxide and sodium silicate. Further preferably, the slag-based solidification system includes the following components in parts by weight: 50-80 parts of blast furnace slag, 0-20 parts of calcium sulfoaluminate, 0-20 parts of tricalcium silicate, 3-5 parts of magnesium oxide, 1-3 parts of aluminum oxide, 1-4 parts of calcium oxide, 3-5 parts of diatomaceous earth, 1-3 parts of sodium silicate, and 2-8 parts of sodium hydroxide.

[0010] The epoxy resin curing system contains 3-aminopropyltriethoxysilane modified nano-silica and graphene oxide. Further preferably, the epoxy resin curing system comprises the following components in parts by weight: 80-90 parts of bisphenol A diglycidyl ether dioxirane, 3-8 parts of dapsone, 0-5 parts of triethylenediamine, 1-3 parts of 3-aminopropyltriethoxysilane modified nano-silica, 0.5-2 parts of graphene oxide, and 0-60 parts of iron ore powder.

[0011] The bridging material is compounded by rigid particles, comet-type fiber filter material and sheet material. The weight ratio of rigid particles, comet-type fiber filter material and sheet material is 1:0.05-0.1:0.02-0.5. The comet-type fiber filter material is composed of comet balls and fibers. The comet balls are spherical through-hole thermosetting resins with a size of 1-5 mm. The fibers are one or more of polytetrafluoroethylene fibers, animal fibers, and plant fibers with a length of 0.5-30 mm. The comet-type fiber filter material is a material that combines fibers and particles together, and plays the role of bridging and reinforcing bars in the plugging slurry.

[0012] Preferably, the rigid particles include the following components in parts by weight: 5-20 parts of calcium carbonate with a particle size not exceeding 0.1 mm, 10-25 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 8-20 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 30-50 parts of walnut shells with a particle size of 1.0-3.0 mm, and 0-15 parts of olive shells with a particle size greater than or equal to 3.0 mm.

[0013] Preferably, the sheet material is one or more of beech wood chips, oak chips, mica chips, glass paper, and sheet phenolic resin, and the sheet material has a thickness of 0.2-2 mm and a length of 1-10 mm.

[0014] The plugging principle of the present invention is: introducing a positively charged solidifying material into the plugging slurry, so that the plugging slurry is positively charged and the surface of the leaking layer is negatively charged. The potential change is generated by the action of the charges, and the mutual attraction causes the solidifying material in the plugging slurry to remain on the surface of the leaking layer. Due to the friction, the migration speed of large particles in the leaking layer is slowed down, and they are gradually accumulated in the leaking layer to form a barrier. Since the barrier has been formed, under the action of the formation pressure difference, the plugging slurry will gradually lose water, and the concentration of the solidifying material in the leaking layer channel will increase. After a certain period of time, the plugging layer forms a high-strength solidified body, ensuring the plugging effect of the leaking layer.

[0015] Compared with the prior art, the present invention is beneficial in that:

[0016] (1) The plugging slurry of the present invention is added with a positively charged solidifying material, which enhances the retention capacity of the plugging slurry in the leaking layer by interacting with the negative charge on the surface of the leaking layer, especially the solidifying material in the plugging slurry, thereby ensuring the retention effect.

[0017] (2) The present invention combines solidified plugging materials and bridging plugging materials, and adopts a retention-bridging-filling-solidification method to ensure the plugging effect.

[0018] (3) The plugging slurry of the present invention uses a small amount of solidifying material and does not solidify during the mixing process, thereby ensuring the safety of the on-site slurry preparation and pumping operations.

[0019] (4) The method of the present invention has a wide range of applications and can be applied to plugging different leakage formations, including permeable formations, fractured formations, fracture-cavity formations, broken formations, low-pressure formations and other complex formations.

[0020] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0021] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0022] Example 1

[0023] A solidified bridging plugging slurry: based on the weight of water, the weight of calcium bentonite accounts for 1% of the weight of water, the weight of the cement-based solidifying system accounts for 20% of the weight of water, and the weight of the bridging material accounts for 15% of the weight of water. Calcium bentonite, cement-based solidifying system, and bridging material are added to water in sequence, and after being stirred evenly, a solidified bridging plugging slurry is obtained.

[0024] The cement curing system formula and preparation method include the following components by weight: 75 parts of oil well G grade cement, 0.5 parts of nano aluminum silicate, 3 parts of nano silicon dioxide, 0.5 parts of xanthan gum, 4 parts of calcium oxide, 15 parts of microsilica powder, and 2 parts of floating beads. The components are mixed evenly to obtain the cement curing system.

[0025] The bridging material formula and preparation method include the following components in parts by weight: 10 parts of calcium carbonate with a particle size of ≤0.1 mm, 20 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 15 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 48 parts of walnut shells with a particle size of 1.0-3.0 mm, 7 parts of olive shells with a particle size of ≥3.0 mm, 0.05 parts of comet fiber filter material (comet ball diameter 3 mm, polytetrafluoroethylene fiber length 10 mm), 0.3 parts of beech wood chips (thickness 1.2 mm, length 8 mm). The components are mixed evenly to obtain the bridging material.

[0026] Example 2

[0027] A solidified bridging plugging slurry: based on the weight of water, the weight of calcium bentonite accounts for 1% of the weight of water, the weight of the slag solidification system accounts for 25% of the weight of water, and the weight of the bridging material accounts for 15% of the weight of water. The calcium bentonite, the slag solidification system, and the bridging material are added to the water in sequence, and after being stirred evenly, the solidified bridging plugging slurry is obtained.

[0028] The formula and preparation method of the slag solidification system include the following components in parts by weight: 72 parts of blast furnace slag, 7 parts of calcium sulfoaluminate, 3 parts of tricalcium silicate, 4 parts of magnesium oxide, 1 part of aluminum oxide, 3 parts of calcium oxide, 5 parts of diatomaceous earth, 2 parts of sodium silicate, and 3 parts of sodium hydroxide. The components are mixed evenly to obtain the slag solidification system.

[0029] The bridging material formula and preparation method include the following components in parts by weight: 6 parts of calcium carbonate with a particle size of ≤0.1 mm, 24 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 20 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 40 parts of walnut shells with a particle size of 1.0-3.0 mm, 10 parts of olive shells with a particle size of ≥3.0 mm, 0.05 parts of comet fiber filter material (comet ball diameter of 4 mm, plant fiber length of 10 mm), 0.3 parts of mica flakes (thickness of 1.2 mm, length of 8 mm). The components are mixed evenly to obtain the bridging material.

[0030] Example 3

[0031] A solidified bridging plugging slurry: based on the weight of water, the weight of calcium bentonite accounts for 1% of the weight of water, the weight of epoxy resin curing system accounts for 15% of the weight of water, and the weight of bridging material accounts for 15% of the weight of water. Calcium bentonite, epoxy resin curing system, and bridging material are added to water in sequence, and after being stirred evenly, a solidified bridging plugging slurry is obtained.

[0032] The epoxy resin curing system formula and preparation method include the following components in parts by weight: 86 parts of bisphenol A diglycidyl ether dioxirane, 4 parts of dapsone, 0.5 parts of triethylenediamine, 3 parts of 3-aminopropyltriethoxysilane modified nano-silica, 1.5 parts of graphene oxide, and 5 parts of iron ore powder. The components are mixed evenly to obtain the epoxy resin curing system.

[0033] The bridging material formula and preparation method include the following components in parts by weight: 12 parts of calcium carbonate with a particle size of ≤0.1 mm, 20 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 15 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 45 parts of walnut shells with a particle size of 1.0-3.0 mm, 8 parts of olive shells with a particle size of ≥3.0 mm, 0.05 parts of comet fiber filter material (the diameter of the comet ball is 4 mm, and the length of the plant fiber is 10 mm), and 0.3 parts of oak chips (thickness 1.2 mm, length 8 mm). The components are mixed evenly to obtain the bridging material.

[0034] Comparative Example 1

[0035] A plugging slurry formula and preparation method: based on the weight of water, the weight of calcium bentonite accounts for 1% of the weight of water, and the weight of cement-based solidifying system accounts for 20% of the weight of water. The calcium bentonite and cement-based solidifying system are added to water and stirred evenly to obtain the plugging slurry.

[0036] The formula and preparation method of cement curing system: comprising the following components by weight: 75 parts of oil well G grade cement, 0.5 parts of nano aluminum silicate, 3 parts of nano silicon dioxide, 0.5 parts of xanthan gum, 4 parts of calcium oxide, 15 parts of micro silicon, and 2 parts of floating beads. The components are mixed evenly to obtain the cement curing system.

[0037] Comparative Example 2

[0038] A plugging slurry formula and preparation method: based on the weight of water, the weight of calcium bentonite accounts for 1% of the weight of water, and the weight of bridging material accounts for 15% of the weight of water. Calcium bentonite and bridging material are added to water and stirred evenly to obtain plugging slurry.

[0039] The bridging material formula and preparation method include the following components in parts by weight: 10 parts of calcium carbonate with a particle size of ≤0.1 mm, 20 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 15 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 48 parts of walnut shells with a particle size of 1.0-3.0 mm, 7 parts of olive shells with a particle size of ≥3.0 mm, 0.05 parts of comet fiber filter material (comet ball diameter 3 mm, polytetrafluoroethylene fiber length 10 mm), 0.3 parts of beech wood chips (thickness 1.2 mm, length 8 mm). The components are mixed evenly to obtain the bridging material.

[0040] Comparative Example 3

[0041] On the basis of Example 1, the three components of nano aluminum silicate, nano silicon dioxide and calcium oxide in the cement curing system formula are removed. That is, the cement curing system formula is: 75 parts of oil well G grade cement, 0.5 parts of xanthan gum, 15 parts of microsilica powder, and 2 parts of floating beads. The components are mixed to obtain a cement curing system.

[0042] Comparative Example 4

[0043] On the basis of Example 1, the comet fiber filter material in the bridging material formula is removed. That is, the bridging material formula is: 10 parts of calcium carbonate with a particle size of ≤0.1 mm, 20 parts of calcium carbonate with a particle size of 0.1-0.5 mm, 15 parts of calcium carbonate with a particle size of 0.5-1.0 mm, 48 parts of walnut shells with a particle size of 1.0-3.0 mm, and 7 parts of olive shells with a particle size of ≥3.0 mm. The components are mixed evenly to obtain the bridging material.

[0044] The performance test is as follows:

[0045] (1) Zeta potential test:

[0046] First, a Zeta potential analyzer was used to test the Zeta potential of the plugging slurries prepared in Examples 1 to 3 and Comparative Examples 1 to 4. The test results are shown in Table 1.

[0047] Take the on-site core, place it in an oven at 120°C and dry it for 24 hours, then crush it into fine particles with a particle size of ≤0.1mm, add the fine particles into water and stir evenly, mix the particles and water in a weight ratio of 2:1, and then prepare the rock chip slurry. Test the Zeta potential of the rock chip slurry. Then take the plugging slurry prepared in Example 1-Example 3 and Comparative Examples 1-4 and the rock chip slurry in the same weight ratio and mix them respectively. After mixing evenly, test the Zeta potential of the mixed slurry. The test results are shown in Table 1.

[0048] Table 1 Zeta potential test results of plugging slurry

[0049] Serial number Example Zeta potential (mV) 1 Example 1 35.42 2 Example 2 40.59 3 Example 3 23.38 4 Comparative Example 1 34.25 5 Comparative Example 2 -15.86 6 Comparative Example 3 16.13 7 Comparative Example 4 33.62 8 Rock chip slurry -21.72 9 Example 1 + Mixed slurry of rock cuttings slurry 15.18 10 Example 2 + Mixed slurry of rock cuttings slurry 20.84 11 Example 3 + Mixed slurry of rock cuttings slurry 6.96 12 Comparative Example 1 + Mixed Slurry of Rock Cuttings Slurry 12.35 13 Comparative Example 2 + Mixed Slurry of Rock Cuttings Slurry -33.73 14 Comparative Example 3 + Mixed Slurry of Rock Cuttings Slurry -2.25 15 Comparative Example 4 + Mixed Slurry of Rock Cuttings Slurry 15.05

[0050] It can be seen from the data in Table 1 that the Zeta potential of the cured bridging plugging slurries prepared in Examples 1-3 and Comparative Example 1 are all positive potentials. The plugging slurry in Comparative Example 2 does not contain a curing material, and its Zeta potential is negative, indicating that the addition of a curing material can change the potential of the plugging slurry from a negative potential to a positive potential. The Zeta potential test results of the cuttings slurry and the mixture of the cuttings slurry and each plugging slurry show that the cured bridging plugging slurry can change the Zeta potential of the cuttings surface through adsorption, which indirectly indicates that the curing material in the cured bridging plugging slurry can have a retention effect on the surface of the leaking layer through potential changes. The cement curing system formula in the plugging slurry in Comparative Example 3 does not contain nano-aluminum silicate, nano-silicon dioxide and calcium oxide. Compared with Example 1, the Zeta potential of the plugging slurry is reduced, indicating that nano-aluminum silicate, nano-silicon dioxide and calcium oxide affect the potential stability of the plugging slurry. The plugging slurry in Comparative Example 4 does not contain comet-type fiber filter material. Compared with Example 1, the Zeta potential of the plugging slurry does not change significantly, indicating that the comet-type fiber filter material does not affect the Zeta potential of the plugging slurry.

[0051] (2) Evaluation of plugging effect:

[0052] A hollow steel pipe with external threads at the upper and lower ends is specially made. The inner diameter of the hollow steel pipe is 30mm and the length is 800mm. The steel pipe is filled with rock cuttings with a particle size of 10-20mm and a filling length of 200mm to simulate the leakage formation. The steel pipe is equipped with a pressure test thread cover. During the pressure test, a 10mm small hole is opened in the middle of the pressure test thread cover at the lower end as the filtrate outlet. The center of the pressure test thread cover at the upper end is opened, and the opening is connected to the pressure test pipeline. The plugging effect of the plugging slurry of Examples 1-3 and Comparative Examples 1-4 was tested respectively. First, pour a plugging slurry until the steel pipe is full, connect the pressure test pipeline, and drive the plugging slurry into the gaps in the cuttings at 0.1 MPa. When the outlet filtrate reaches 30 mL, stop squeezing, place the steel pipe as a whole in a 90°C oven and wait for solidification for 24 hours before taking it out. Use the pressure test pump to pressurize the pressure test liquid into the steel pipe through the upper air valve, and increase the gradient by 2 MPa every 30 minutes. Observe the leakage of the filtrate outlet under the steel pipe to judge the plugging effect of the test slurry. The test results are shown in Table 2.

[0053] Table 2. Experimental results of plugging effect of plugging slurry

[0054]

[0055] Note: The pressure test liquid is clean water, and the volume of clean water is 1000mL.

[0056] It can be seen from the data in Table 2 that the pressure bearing capacity of the cured bridging plugging slurry prepared in Examples 1-3 after plugging the leaking layer is greater than 20MPa, and the pressure bearing capacity of the plugging slurry prepared in Comparative Examples 1 and 2 for plugging the leaking layer is ≤4MPa, resulting in a complete leakage, and the plugging effect is not good. This is because there is only curing material in Comparative Example 1 and the concentration of the curing material is low, and the strength of the filled leaking layer after curing is poor, resulting in an unsatisfactory pressure bearing effect, while there is only bridging material in Comparative Example 2, and the larger gaps cannot be completely filled, resulting in low pressure bearing capacity, or even no pressure bearing. By comparing the pressure bearing capacity of the plugging slurry, it is shown that only by using both the curing material and the bridging material can the plugging effect be ensured. The cumulative leakage amount of Comparative Examples 3 and 4 increased, indicating that nano-aluminum silicate, nano-silicon dioxide, calcium oxide and comet-type fiber filter materials all affect the plugging effect of the plugging slurry. Among them, the cement curing system formula in the plugging slurry of Comparative Example 3 does not contain nano aluminum silicate, nano silicon dioxide and calcium oxide, so the Zeta potential of the plugging slurry is reduced, which affects the potential stability of the plugging slurry, and then the charge interaction between the plugging slurry and the surface of the leaking layer is significantly weakened, and the mutual attraction is weak, so that the curing material in the plugging slurry cannot be retained on the surface of the leaking layer, thereby affecting the plugging effect. In Comparative Example 4, due to the lack of the comet fiber filter material component, there is a lack of sufficient bridging and reinforcement, which makes the plugging effect of the plugging slurry worse.

[0057] In short, the plugging method of the present invention is suitable for plugging complex formations such as fractured formations, low-pressure formations, and broken formations. The solidified material in the plugging slurry is retained and solidified by the potential change caused by the surface charge of the leaking layer, and the bridging material forms a high-strength plugging layer with the bridging filling effect, thereby ensuring the plugging effect and solving the problem that the existing plugging technology has poor plugging effect on complex formations.

[0058] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A positive electric retention filtration accumulation solidification plugging method, characterized in that: A positively charged solidified bridging plugging slurry is injected into the formation for plugging; the solidified bridging plugging slurry is composed of water, calcium bentonite, solidifying material and bridging material; The curing material is any one of a cement curing system, a slag curing system, and an epoxy resin curing system; The cement curing system contains nano aluminum silicate, nano silicon dioxide and calcium oxide; The slag solidification system contains magnesium oxide, aluminum oxide, calcium oxide and sodium silicate; The epoxy resin curing system contains 3-aminopropyltriethoxysilane-modified nano-silica and graphene oxide; The bridging material is compounded by rigid particles, comet-type fiber filter material and sheet material. The comet-type fiber filter material is composed of comet balls and fibers. The comet balls are spherical through-hole thermosetting resins with a size of 1-5 mm. The fibers are one or more of polytetrafluoroethylene fibers, animal fibers, and plant fibers with a length of 0.5-30 mm.

2. The positive electric retention filtration loss accumulation solidification plugging method according to claim 1, characterized in that: In the solidified bridging plugging slurry, based on the weight of water, the weight of calcium bentonite accounts for 1-3% of the weight of water, the weight of solidifying material accounts for 15-30% of the weight of water, and the weight of bridging material accounts for 10-30% of the weight of water.

3. The positive electric retention filtration loss accumulation solidification plugging method according to claim 2, characterized in that: The cement curing system comprises the following components in parts by weight: 60-80 parts of oil well G grade cement, 0.5-1.5 parts of nano aluminum silicate, 1-3 parts of nano silicon dioxide, 0.5-1 parts of xanthan gum, 3-5 parts of calcium oxide, 5-15 parts of micro silicon, and 0-5 parts of floating beads.

4. The positive electric retention filtration loss accumulation solidification plugging method according to claim 2, characterized in that: The slag solidification system comprises the following components in parts by weight: 50-80 parts of blast furnace slag, 0-20 parts of calcium sulfoaluminate, 0-20 parts of tricalcium silicate, 3-5 parts of magnesium oxide, 1-3 parts of aluminum oxide, 1-4 parts of calcium oxide, 3-5 parts of diatomaceous earth, 1-3 parts of sodium silicate, and 2-8 parts of sodium hydroxide.

5. The positive electric retention filtration loss accumulation solidification plugging method according to claim 2, characterized in that: The epoxy resin curing system comprises the following components in parts by weight: 80-90 parts of bisphenol A diglycidyl ether diethylene oxide, 3-8 parts of dapsone, 0-5 parts of triethylenediamine, 1-3 parts of 3-aminopropyltriethoxysilane modified nano silicon dioxide, 0.5-2 parts of graphene oxide, and 0-60 parts of iron ore powder.

6. The positive electric retention filtration loss accumulation solidification plugging method according to claim 1, characterized in that: The weight ratio of the rigid particles, the comet-type fiber filter material and the sheet material is 1:0.05-0.1:0.02-0.

5.

7. The positive electric retention filtration loss accumulation solidification plugging method according to claim 6, characterized in that: The rigid particles include the following components in parts by weight: 5-20 parts of calcium carbonate with a particle size not exceeding 0.1mm, 10-25 parts of calcium carbonate with a particle size of 0.1-0.5mm, 8-20 parts of calcium carbonate with a particle size of 0.5-1.0mm, 30-50 parts of walnut shells with a particle size of 1.0-3.0mm, and 0-15 parts of olive shells with a particle size greater than or equal to 3.0mm.

8. The positive electric retention filtration loss accumulation solidification plugging method according to claim 6, characterized in that: The sheet material is selected from one or more of beech wood chips, oak chips, mica chips, glass paper, and sheet phenolic resin. The sheet material has a thickness of 0.2-2 mm and a length of 1-10 mm.